PENGARUH KECERDASAN EMOSIONAL TERHADAP KEMAMPUAN MENULIS ARGUMENTASI SISWA DI SMP NEGERI 1 TANJUNGBALAI - Hajar, Fata Ibnu (Jurnal Pelangi : Research of Education and Development, 2018)
Writing arguments as one type of writing that aims to express ideas or opinions based on perceived experiences and observations. In addition, lifting things closer to the students makes students easy in expressing their ideas because the emotional role is very tight there. The purpose of this study is to prove the Influence of Emotional Intelligence Against the ability of writing arguments for students of SMP 1 Tanjungbalai. The population of this study were students of SMP  1 Tanjungbalai with a sample of 64 grade VII students from the school. The data analysis used linear regression and correlation test to find out the functional relationship and the closeness between the two variables. The results of this study showed that emotional intelligence significantly influence the ability of writing arguments. Meanwhile, the relationship between emotional intelligence and the ability of writing arguments is very high with correlation coefficient 0.945